THE SIMPLIFIED MORTALITY IN SEVERE SEPSIS IN THE EMERGENCY DEPARTMENT (MISSED) SCORE TO RISK STRATIFY ED SEPSIS. Issue 12 (23rd November 2015) - Sivayoham, N; Holmes, P; Cecconi, M; Rhodes, A
Abstract : Objectives & Background: In patients with sepsis, early intervention in the emergency department (ED) has been shown to reduce mortality. Early treatment requires early risk stratification. The criteria defining shock identifies some of the sickest patients. But not all patients who go on to die present with shock. Other scoring systems are available but they are labour intensive to use in a busy ED. The MISSED (Mortality in Severe Sepsis in the ED) score is a simple and easy to use score that was derived and validated to risk stratify ED patients with sepsis. But the population studied were ED patients admitted to the intensive care unit (ICU). This score has now been refined and simplified. The independent variables associated with mortality are: age ≥65 years, serum albumin ≤27g/l and an international normalised ratio (INR) ≥1.3. The simplified MISSED score ranges from 0 to 3 depending on the number of variables present. We aim to validate the simplified MISSED score in the ED population admitted with sepsis. The primary end point was in-hospital all-cause mortality. The secondary endpoint was the validation of the risk stratification for mortality and ICU admission. Methods: ED patients admitted with a primary diagnosis of presumed infection in the year 2012 were studied. Patients missing data on any of the variables and those on warfarin were excluded. The simplified MISSED score was calculated for each patient. The test characteristics for mortality of the simplified MISSED score and the odds ratios of the high risk groups for the secondary end-points were calculated. Results: 674 patients including 65 deaths were studied. The area under the curve (AUC) for the simplified MISSED score was 0.74 [95% confidence interval (CI) 0.70–0.77]; p<0.0001. The test characteristics for mortality were: sensitivity 93.9% [85–98.3], specificity 37.9% [34.1–41.9], positive predictive value 13.9% [10.8–17.5] and negative predictive value 98.3% [95.7–99.5]. The addition of the septic shock criteria improves the sensitivity to 70.8% [55.9–83]. The odds ratio for mortality for a score≥2 was: 5.01 [2.93–8.57], p<0.0001 and that for ICU admission was 3.00 [1.70–5.28], p=0.0001. The specificity of a score of 3 for mortality is 97.7% (96.2–98.7). Conclusion: The simplified MISSED score could be used in addition to the septic shock criteria to risk stratify septic patients in the ED.